Factor VIII Inhibitors in Mild and Moderate-severity Haemophilia A - Hay, C.R.M.; Ludlam, C.A.; Colvin, B.T.; Hill, F.G.H.; Preston, F.E.; Wasseem, N.; Bagnall, R.; Peake, I.R.; the UK Haemophilia Centre Directors Organisation; on behalf of; Berntorp, E.; Bunschoten, E.P. Mauser; Fijnvandraat, K.; Kasper, C.K.; White, G.; Santagostino, E. (Thrombosis and Haemostasis, 1998)
Twenty six patients with mild or moderate haemophilia A and inhibitors are described. The inhibitor was detected at a median age of 33 years, after a median of 5.5 bleeding episodes. This usually following intensive replacement therapy. The median presenting inhibitor titre was antihuman 11.6 BU/ml, antiporcine 1.45 BU/ml. Plasma basal factor VIII level declined from a median of 0.08 IU/ml to 0.01 IU/ml following the inhibitor development. This caused spontaneous bleeding in 22 and a bleeding pattern similar to acquired haemophilia in 17. Bleeding was often severe and caused two deaths.The inhibitor disappeared spontaneously, or following immune tolerance induction, in 16 cases after a median of 9 months (range 0.5-46), with a return to the original baseline VIIIC level and bleeding pattern accompanied inhibitor loss. The inhibitor persisted in the remainder of the cases over a median period of 99 months (range 17-433 months) of follow-up. Inhibitors are an uncommon complication of mild haemophilia which frequently persist and may be associated with severe, life-threatening, haemorrhage.Forty-one percent of treated haemophilic family members had a history of factor VIII inhibitors, suggesting a familial predisposition to develop inhibitors in these kindreds. Sixteen patients from 11 families were genotyped. Seven different missense mutations affecting the light chain were detected and two in the A2 domain. Five patients from three families had a mutation causing a substitution of Trp2229 by Cys in the C2 domain which appears to predispose to inhibitor formation since 7 of the 18 affected individuals have a history of inhibitor development.